2021
DOI: 10.7759/cureus.20772
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Predictive Value of Preoperative Clinical and Imaging Findings on the Short-Term Outcome of Surgery in Patients Undergoing Lower Lumbar Discectomy

Abstract: Objective: The most common indications for spinal surgery are low back pain and associated disabilities caused by disc herniation. Given the high prevalence of low back pain, the critical nature of pain assessment in these patients, and knowledge about the influencing and predisposing factors, we sought to evaluate the clinical and radiologic findings associated with pain relief and postoperative recovery in patients who underwent bilateral lumbar discectomy.Methods: From March 2016 to October 2020, a prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…Iorio-Morin et al [ 12 ] also identified the following six clinical factors associated with poor back pain improvement after surgery : low expectations, not working, low level of education, female sex, and being married. Additionally, Tabibkhooei et al [ 26 ] reported that higher BMI and neurological claudication are predictive factors for poor reduction in back pain. In the present study, we found that a greater reduction in DH after surgery was associated with greater improvement in postoperative back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Iorio-Morin et al [ 12 ] also identified the following six clinical factors associated with poor back pain improvement after surgery : low expectations, not working, low level of education, female sex, and being married. Additionally, Tabibkhooei et al [ 26 ] reported that higher BMI and neurological claudication are predictive factors for poor reduction in back pain. In the present study, we found that a greater reduction in DH after surgery was associated with greater improvement in postoperative back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing the radiological "normal values" of the lumbar intervertebral disc height is relevant for a number of clinical issues. On the one hand, intervertebral disc height is an important predictor for the development and prognosis of a herniated disc [23,24,25,26,27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Die Kenntnis der radiologischen "Normalwerte" der lumbalen Bandscheibenhöhen ist für eine Reihe von klinischen Fragestellungen relevant. Die Bandscheibenhöhe ist einerseits ein wichtiger Prädiktor für die Entstehung und die Prognose eines Bandscheibenvorfalls [23,24,25,26,27,28].…”
Section: Diskussionunclassified